The fluctuation of peatland water table at Tumbang Nusa, Central Kalimantan - Purwanto Budi Santosa; Muhammad Abdul Qirom (Jurnal GALAM, 2020)
Burnt peatland restoration by planting needs stable hydrological condition for the plant’s growth. Water table fluctuation becoming a challenge in the planting effort on degraded peatland. This research aims to determine the water table on degraded peatland and over burnt peat at Tumbang Nusa Forest for Specific Purposes, Pulang Pisau District, Central Kalimantan Province. The data was analyzed to determine the relationship between precipitation characteristics, water table and land elevation. Water table observation was carried out on several fires starting 1997, 2003, 2006 and 2009. We observed 17 points of water table of the total length of 4 km and 250 m distance between points, started from the river edge up to secondary forests. The level of vegetation cover and condition varied from woody plants with low density and open crown up to woody plants with good canopy cover. The result showed that the water table was closely related with the elevation and distance from canal. The fluctuation was closely related with precipitation. Nevertheless, the rainfall did not directly relate but there was a certain interlude period so that the water table was rising or decreasing. This condition shall be considered in the land rehabilitation by planning the right plant in the right time so that the plants can reach optimum growth